PENGARUH PEMBERDAYAAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT ITHACA RESOURCES JAKARTA - Mochammad Subagio (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2015)
The Influence of Empowerment and Motivation on Employee Performance. The purpose of this study are to analyze and explain the influence of empowerment and motivation on employee performance. This research is an explanatory research type. The sampling technique using census sampling as all employee to be a sampling in this research. The Research place in PT Ithaca Resources Jakarta. The methods of data collection using questionnaires. The data analysis using multiple regression analysis. Research results stated that the empowerment variable are significant influence on performance variable, motivation variable are significant influence on performance variable, empowerment variable and motivation variable have significant influence on performance variable.